Globalization and "minority" cultures : the role of "minor" cultural groups in shaping our global future. - Croisy, Sophie (Studies in international minority and group rights., 2014)
Globalization and "Minority" Cultures: The Role of "Minor" Cultural Groups in Shaping Our Global Future is a collective work which brings to the forefront of global studies new perspectives on the relationship between globalization and the experiences of cultural minorities worldwide.